THE EFFECT OF MARKET ORIENTATION AND MARKET DISRUPTION CAPABILITY ON SOCIAL ENTERPRISES’ PERFORMANCE - Sirawajanakul, Watcharin (Journal of Social Science and Cultural, 2023)
This academic article presents the concepts of social enterprise, Market orientation, and market disruption capability to examine the relationship between these concepts and answer the questions: Do market orientation and market disruption capability affect the performance of social enterprises, and how? This was studied through a literature review. and present the content in a synthetic descriptive form. The structural concept model from the literature synthesis results indicates that focusing on the market is a factor that affects social enterprises' business and social performance, while their ability to adapt to market disruptions is the only factor that directly affects business performance. Aside from that, Additional observations in this study found that integrating both factors together affects both the economic and social performance of social enterprises. And at the end of the article, suggestions are made on how to apply this framework for future research. To develop factors that positively affect the performance of both aspects of social enterprises, the conceptual model will be tested for consistency with empirical data. Therefore, it may be one way to give both variables more theoretical strength. In addition, interviews with social entrepreneurs and those involved in the social enterprise population ecosystem in Thailand It is another way to gain insights to support the creation of knowledge in many dimensions. For policy presentation and implementation of policies for further social and economic development.